Dampak Lingkungan Sosial terhadap Perilaku Antisosial pada Anak Usia 4-6 Tahun - Putri, Roza Sartika; Wigati, Indah; Sartika, Indah Dwi (INCARE, International Journal of Educational Resources, 2024)
This study aims to describe the antisocial behavior of children aged 4-6 years in one of the kindergartens in South Sumatra, describe the social environment of the children, and analyze the impact of the social environment on their antisocial behavior. The research method used is qualitative with a case study approach. Data were collected through observation, interviews, and documentation. The research results show that the antisocial behavior of children includes being difficult to manage, liking to fight, showing hostility, being difficult to be quiet, and being disobedient. The social environment, especially family and peers, significantly influences the emergence of antisocial behavior in children. The study concludes that an unconducive social environment can increase the risk of antisocial behavior in early childhood.